High Concentration of Red Clay as an Alternative for Antibiotics in Aquaculture - Jung, Jaejoon; Jee, Seung Cheol; Sung, Jung-Suk; Park, Woojun (Journal of microbiology and biotechnology, 2016)
The use of antibiotics in aquaculture raises environmental and food safety concerns because chronic exposure of an aquatic ecosystem to antibiotics can result in the spread of antibiotic resistance, bioaccumulation of antibiotics in the organisms, and transfer of antibiotics to humans. In an attempt to overcome these problems, high-concentration red clay was applied as an alternative antibiotic against the following common fish pathogens: Aeromonas salmonicida, Vibrio alginolyticus, and Streptococcus equinus. The growth of A. salmonicida and V. alginolyticus was retarded by red clay, whereas that of S. equinus was promoted. Phase contrast and scanning electron microscopy analyses confirmed the attachment of red clay on cell surfaces, resulting in rapid gravitational removal and cell surface damage in both A. salmonicida and V. alginolyticus, but not in S. equinus. Different cell wall properties of grampositive species may explain the unharmed cell surface of S. equinus. Significant levels of oxidative stress were generated in only the former two species, whereas significant changes in membrane permeability were found only in S. equinus, probably because of its physiological adaptation. The bacterial communities in water samples from Oncorhynchus mykiss aquacultures supplemented with red clay showed similar structure and diversity as those from oxytetracycline-treated water. Taken together, the antibiotic effects of high concentrations of red clay in aquaculture can be attributed to gravitational removal, cell surface damage, and oxidative stress production, and suggest that red clay may be used as an alternative for antibiotics in aquaculture.